Sword and Buckler in Masorah Figurata: Traces of Early Illuminated Fight Books in the Micrography of Bible, BnF, MS héb. 9 - Offenberg, Sara (Acta Periodica Duellatorum, 2021)
Two manuscripts produced in early fourteenth-century German lands reflect similar iconography of the fighting with Sword and Buckler; one is the well-known fencing manual, Leeds, Royal Armouries, MS I. 33, produced ca. 1320, and the other is a Hebrew manuscript of the Bible, Paris, Bibliothèque nationale de France héb. 9, made in 1304, that will be the focus of this article. This preliminary research intends to demonstrate how Hebrew illuminated manuscripts can shed more light on the study of fight books iconography.